Dampak Meninggalkan Istri Bertahun-tahun Tanpa Dinafkahi terhadap Status Suami Menurut Imam Syafi'i - Dina Oktavia Waode; Abdullah Sani K (Peduli Riset dan Pengabdian Masyarakat, 2024)
This study aims to analyze the law of leaving a wife for years without maintenance based on the views of Imam Syafi'i, especially in the situation of a mafqud (missing) husband. This research uses a qualitative approach with a library research method, which collects data from various literature sources such as books, scientific works, and scholarly opinions. Data collection techniques are carried out through literature studies that focus on Islamic legal studies related to the husband's responsibility towards his wife. The data analysis techniques used include descriptive and comparative analysis, which aims to describe and compare the views of various scholars, especially from the Syafi'i school of thought. The results showed that according to Imam Syafi'i, a husband is obliged to provide maintenance to his wife as long as the marriage is still valid, even though he is far away or his whereabouts are unknown. In the case of a mafqud husband, Imam Syafi'i argues that the wife can sue for divorce if the husband does not return for a long time. Imam Shafi'i also distinguishes between the opinions in qaul qadim and qaul jadid regarding the time limit for the wife to wait. In qaul qadim, the time limit is 90 years, while in qaul jadid, the wife must wait until there is certainty of the husband's death. If the husband comes after the wife remarries, the second marriage can be annulled. This result underscores the importance of the balance of rights and obligations in marriage from the perspective of Islamic law.